Mighty Jack and Zita the spacegirl - Hatke, Ben (First Second, 2019)
In this crossover adventure, two mighty heroes join forces. Jack and Lilly meet Zita the Spacegirl who warns them of an interstellar invasion force that threatens to end humanity. With Earth's gate failing and the alien menace on the verge of getting in, Jack, Lilly, and Zita must team up to find a solution to save the world.